Sojusznicy króla czy wielkiego mistrza? Książęta śląscy w obliczu wojny Polski z zakonem krzyżackim w 1433 roku = Allies of the King or the Grand Master? Silesian princes in the face of the Poland ?s war with the Teutonic Order in 1433 - Karp, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
From 1425 onwards the Hussite field armies crossed the Silesian borders many times and their marches were marked by plunder, fire, depopulation of this wealthy region. The principalities of Lower and Upper Silesia were the part of Bohemian kingdom, but Hussite military expeditions - "glorious raids" as they came to be called - destroy them as same as the neighbouring countries of Germany, Austria or Hungary.
Keywords: husyci; średniowieczna Polska; zakony rycerskie; Hussites; medieval Poland; the Knights Orders